Analysis of stress block parameters for high strength concrete - Singh, Brijesh; Patel, Vikas; Ojha, P N; Arora, V V (Journal of Asian Concrete Federation, 2020)
In Indian Standard code IS: 456-2000 for concrete of grades higher than M55, the design parameters given may not be applicable as structural behaviour of concrete changes as strength of concrete increases. Different international standards give different stress block parameters which can be reduced to these two basic factors. In this paper, stress block parameters K (strength reduction factor) and k2 (factor for the depth of resultant compressive force) were calculated from experimental strain values considering the stress-strain curve as parabolic for lower grades and as linear for higher grades. Also, the method and approach for the calculation of stress block parameters have been worked out. The method so proposed is compared with the model proposed in European design standard EC: 02-2004 by transforming the European stress block parameters to the basic parameters used. Also, the effect of the shape of the stress-strain curve and value of ultimate strain in concrete on stress block parameters and moment capacity of the members was analyzed by working on the representative section. The method or approach so proposed will be useful to understand and compare flexural design philosophies used in different international standards by reducing the stress block parameters to two basic factors.